Theoretical Analysis of Institutional dimension of Indian democracy - Borah, Pori (International Journal of Psychosocial Rehabilitation, 2020)
Democracy stands for that form of government in which ultimate power rests in the hands of common people. Indian democracy is considered to be the largest democracy in the world. In a democratic nation institution plays a very pivotal role. With the establishment of this formal setup, an attempt is made to fulfill the welfare goals for common people. The institutional dimension of India includes political, economic and social spheres of the society that requires the involvement of the common people either directly or indirectly. In order to safeguard the Constitution, which is the supreme law of the land, the institutions present in the political sphere of the country perform numerous functions. Economic institutions are inevitable for the country’s economic prosperity. Some of these institutions are run by the government of India and some are run by private entrepreneurs. However, institutions in the social sphere are concerned more about those issues of the common people that are either neglected or skipped by the government authority and to bring them into light with the help of strong public opinion or active mass media. Institutions present in India have so far strengthened their base that without them it is quite impossible to run the State.